2018
DOI: 10.1108/itp-10-2016-0237
|View full text |Cite
|
Sign up to set email alerts
|

Excessive social media use at work

Abstract: Purpose The purpose of this paper is to explore the effects of excessive social media use on individual job performance and its exact mechanism. An extended stressor–strain–outcome research model is proposed to explain how excessive social media use at work influences individual job performance. Design/methodology/approach The research model was empirically tested with an online survey study of 230 working professionals who use social media in organizations. Findings The results revealed that excessive soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
146
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(206 citation statements)
references
References 76 publications
14
146
1
1
Order By: Relevance
“…In this manner they join six clusters (intra-cohesional), with a dominant presence of techno-scientific pragmatism in only one cluster. Regarding the psychological approach, among the prolific authors Cao and other Chinese and Korean authors stand out, highlighting the performance and centrality in scientific production accomplished by the University of Science and Technology of China [39,[110][111][112][113][114]. Thus, the first and second author in the world maintain dissimilar approaches, without presenting joint works and having, as their only link, other researchers from the City University of Hong Kong.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this manner they join six clusters (intra-cohesional), with a dominant presence of techno-scientific pragmatism in only one cluster. Regarding the psychological approach, among the prolific authors Cao and other Chinese and Korean authors stand out, highlighting the performance and centrality in scientific production accomplished by the University of Science and Technology of China [39,[110][111][112][113][114]. Thus, the first and second author in the world maintain dissimilar approaches, without presenting joint works and having, as their only link, other researchers from the City University of Hong Kong.…”
Section: Discussionmentioning
confidence: 99%
“…These feelings may ultimately increase technostress caused by the usage of social media, and thereby result in decreased job performance [37]. Therefore, the phenomenon of excessive use of social media in the workplace has become a significant problem for organizations and deserves more attention from scholars [39].…”
Section: Technostress and The Use Of Social Media In The Workplacementioning
confidence: 99%
“…The China Internet Network Information Center (CNNIC) released the social media users' behavior research report, which found that enterprise/company employee respondents accounted for 31% of social media users, which was the highest percentage of all users [China Internet Network Information Center (CNNIC), 2016]. In organizations, employees use many social media platforms for sharing and communicating (Yu et al, 2018). Many studies have shown that using social media platforms can enhance individual job performance and productivity in the workplace (Aral et al, 2013;Moqbel et al, 2013;Alalwan et al, 2017;Cao and Ali, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important with the surge in mobile device ownership [2] and the associated level of excessive usage [9], [17], [18] among undergraduates. Excessive usage is also described as compulsive usage or overreliance on technology [19]. Excessive refers to the high level of constant usage of mobile apps that are associated with anxiety and stress [20]- [23].…”
Section: Introductionmentioning
confidence: 99%